2016
DOI: 10.1039/c6cc01430e
|View full text |Cite
|
Sign up to set email alerts
|

‘Clickable’ ZnO nanocrystals: the superiority of a novel organometallic approach over the inorganic sol–gel procedure

Abstract: We demonstrate for the first time a highly efficient Cu(i)-catalyzed alkyne-azide cycloaddition reaction on the surface of ZnO nanocrystals with retention of their photoluminescence properties. Our comparative studies highlight the superiority of a novel self-supporting organometallic method for the preparation of brightly luminescent and well-passivated ZnO nanocrystals over the traditional sol-gel procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 33 publications
(10 reference statements)
3
36
0
Order By: Relevance
“…[2,5] Althought he sol-gelp rocess is versatile, it has some significant impediments.I np articular,t he rapid nucleation and subsequent growth in the quantum size regime are kinetically controlled, [9] and this makes it difficult to terminate the reaction at the desired stage of particle growth and lowers the uniformity of particle surface composition. [11] The imprecise character of the resulting inorganic/organic interface is likely responsible for the relativelyf ast photoluminescence (PL) decay (i.e.,f or ZnO NCs prepared by the sol-gel procedure, PL lifetimes in the range of picoseconds were reported [12] ). Thus, the resulting NCs are usually not stable during storagea nd tend to grow with time, which greatly limits their applications.A dditionally,t he ZnO NCs prepared by the traditional inorganic wet method are usually insufficiently shielded against the chemical environment, which explainst heir inefficient functionalization by click chemistry in-volvingC u I -catalyzed azide-alkyne cycloaddition (CuAAC) with retention of the photoluminescence properties.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[2,5] Althought he sol-gelp rocess is versatile, it has some significant impediments.I np articular,t he rapid nucleation and subsequent growth in the quantum size regime are kinetically controlled, [9] and this makes it difficult to terminate the reaction at the desired stage of particle growth and lowers the uniformity of particle surface composition. [11] The imprecise character of the resulting inorganic/organic interface is likely responsible for the relativelyf ast photoluminescence (PL) decay (i.e.,f or ZnO NCs prepared by the sol-gel procedure, PL lifetimes in the range of picoseconds were reported [12] ). Thus, the resulting NCs are usually not stable during storagea nd tend to grow with time, which greatly limits their applications.A dditionally,t he ZnO NCs prepared by the traditional inorganic wet method are usually insufficiently shielded against the chemical environment, which explainst heir inefficient functionalization by click chemistry in-volvingC u I -catalyzed azide-alkyne cycloaddition (CuAAC) with retention of the photoluminescence properties.…”
Section: Introductionmentioning
confidence: 99%
“…More than ad ecade ago,C haudret and co-workers made use of highly oxophilic dicyclohexylzinc as the organometallic precursor to produce ZnO NCs coated by L-typel igands. [11,20] The resulting ZnO NCs have au nique nanocrystal/ligand interface, as documented by their processability at water/air interfaces [20a,b] and effective functionalization by the CuAACr eaction with retention of their PL. [18] The resulting water-soluble ZnO NCs exhibited unprecedentedu ltralong-lived electron-hole separation (up to 2.2 ms) [18a] and, by taking advantage of the exceptional properties of ZnO NCs modifiedw ith ao ligoethylene glycol carboxylate shell, we created an anohybrid system for H 2 evolution under visible-light irradiation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter issue has hitherto been unappreciated, and recent studies have indicated that the sol–gel process leads to the formation of ZnO NCs with disordered “swollen” organic shells . Moreover, the permeability and instability of organic ligand shells have also been documented by their fluorescence quenching following functionalization by the copper(I)‐catalyzed Huisgen “click” reaction (CuAAC) …”
Section: Introductionmentioning
confidence: 99%
“…have reported an efficient organometallic route that involves the hydrolysis of a mixture of a dialkylzinc (ZnR 2 ) with a zinc carboxylate (Zn(O 2 CR′) 2 ), which proceeds at ambient temperature and without post‐synthesis refinement . As part of ongoing studies, our group has developed an alternative non‐external‐surfactant‐assisted self‐supporting organometallic strategy using RZn(X)‐type precursors, which affords well‐defined and high‐quality ZnO NCs coated by a shell composed of strongly anchored carboxylates as monoanionic X‐type ligands . The impermeability of the organic ligand shell was independently confirmed by the fluorescence stability of ZnO NCs during their surface modification by the CuAAC method and the solution processability of discrete ZnO NCs into photoactive semiconducting thin films at the water/air interface as well as their ultra‐long‐lived luminescence .…”
Section: Introductionmentioning
confidence: 99%